Chemistries and capabilities of photo-formable and photoreversible crosslinked polymer networks. Issue 9 (17th May 2019) - Hughes, T.; Simon, G. P.; Saito, K.
Abstract : We investigate how the application of photocuring has addressed unique challenges through inherent benefits of the methodology or inventive chemistries. Abstract : Photocuring has been found to be highly useful in a diverse range of fields, such as coatings, protein coupling, liquid crystals, photoresists, drug delivery and hydrogels. Each application and use brings new challenges, with the inventive solutions contributing to a varied catalog of chemistries. The first part of this review overviews a range of the most widely-used and inventive chemistries employed to form crosslinked networks over the last decade, as well as detailing their mechanism, limitations and benefits. The second part of this review investigates the application of photoreversibly-cured crosslinked networks as photo-healable polymers, an application that exemplifies the capabilities of photoreversible chemistry.